The Impact of Service Quality, Facilities, and Location on Customer Satisfaction at PT Satya Trinadi Komira Perkasa in Tangerang Branch - Sutarjo Sutarjo; Wanda Yulia Utami; Ristanto Ristanto (Jurnal Ilmiah Manajemen Kesatuan, 2024)
This research examines the influence of service excellence, resource availability, and locational strategy on customer satisfaction at PT Satya Trinadi Komira Perkasa, with a primary focus on its Tangerang Regency branch. A descriptive approach was implemented, utilizing questionnaires as the primary tool for data gathering. The study involved 97 participants, selected using incidental sampling methods. Data analysis was performed through multiple linear regression, facilitated by SPSS 26 software. The results from partial testing indicate that service excellence and resource availability significantly enhance customer satisfaction, while locational strategy also holds considerable impact. Simultaneously, the findings from combined tests demonstrate that service excellence, resource availability, and locational strategy collectively have a profound effect on customer satisfaction, confirming Ha and rejecting Ho. The research emphasizes the pivotal role of service excellence in meeting and exceeding consumer expectations, fostering loyalty, and building a competitive edge. Adequate facilities and a strategically selected location complement service delivery, contributing to an improved customer experience. Businesses aiming to maintain market relevance must prioritize these factors. The study highlights the critical importance of aligning customer satisfaction strategies with operational efficiencies to secure sustainable growth.